Peningkatan Literasi Digital dan Keamanan Siber Bagi Siswa SMAS BPD Tobelo Selatan - Pattiasina, Tiska; Luturmas, Join Rachel; Fredriksz, Grace; Salhuteru, Andrie CH; Nunumete, Laura S; Matuankotta, Febiola (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The development of digital technology has had a significant impact on high school students, particularly in their use of the internet and social media. However, the lack of digital literacy and cybersecurity awareness remains a problem that needs to be addressed. This community service activity aims to improve digital literacy and cybersecurity understanding among students at SMAS BPD Tobelo Selatan. The methods used included lectures, discussions, and QA sessions, with material covering digital literacy, social media ethics, cyberbullying, hoaxes, and personal data protection. The activity was held offline on September 7, 2025, with 15 students participating. Evaluation was conducted using a Guttman Scale questionnaire to assess participant responses to the activity. Results showed that all students (100%) expressed satisfaction, indicating that the activity successfully improved students' understanding of digital literacy and cybersecurity. Therefore, this community service activity makes a positive contribution in equipping students with wise, safe, and responsible digital skills to face the challenges of the digital era.